Development of Innovative Learning Assessment Modules on Augmented Reality-Based Space Building - Ian Harum Prasasti; Donny Muda Priyangan; Hera Fransiska (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Learning assessment aims to monitor the progress of the learning process and check the fulfillment of competence against learning outcomes to provide value for the learning process and results. The Augmented Reality (AR) learning assessment module aims to test students' competence in geometrical material. AR is needed to help students visualize 2-dimensional shapes into three dimensions. The purpose of this research is to develop an innovative learning assessment module based on augmented reality systems to test student competencies. This type of research is Research and Development (R & D). The sample of this research is the seventh-grade students of SMP N 01 Kalirejo in Central Lampung Regency. The model used is an adaptation of Plomp, which includes preliminary examination, prototyping and assessment. The results of this study are that the instrument has met the requirements of validity and reliability and even has practical value in its use. This will provide positive benefits for an objective, measurable, and comprehensive assessment process on the final ability of student learning outcomes. Utilization of learning media using AR can stimulate students' mindset in critical thinking. AR learning media can visualize abstract concepts for understanding and structure an object model that allows AR as a more effective medium.